Spin Splitting Spectroscopy of Heavy Quark and Antiquarks Systems - Hesham Mansour; Ahmed Gamal; M. Abolmahassen (Advances in High Energy Physics)
Phenomenological potentials describe the quarkonium systems like cc¯,bb,¯ and b¯c where they give a good accuracy for the mass spectra. In the present work, we extend one of our previous works in the central case by adding spin-dependent terms to allow for relativistic corrections. By using such terms, we get better accuracy than previous theoretical calculations. In the present work, the mass spectra of the bound states of heavy quarks  cc¯, bb¯, and 𝐵𝑐 mesons are studied within the framework of the nonrelativistic Schrödinger equation. First, we solve Schrödinger’s equation by Nikiforov-Uvarov (NU) method. The energy eigenvalues are presented using our new potential. The results obtained are in good agreement with the experimental data and are better than the previous theoretical estimates.